577 Bisoprolol for the treatment of symptomatic patients with obstructive hypertrophic cardiomyopathy. (8th December 2021) - Monda, Emanuele; Lioncino, Michele; Palmiero, Giuseppe; Rubino, Marta; Cirillo, Annapaola; Verrillo, Federica; Fusco, Adelaide; Caiazza, Martina; Mazzella, Marialuisa; Moscarella, Elisabetta; Dongiglio, Francesca; Sepe, Joseph; et al.
Abstract: Aims: To evaluate to role of bisoprolol to control symptoms and left ventricular outflow tract obstruction (LVOTO) in a consecutive cohort of adults with hypertrophic cardiomyopathy (HCM). Methods and results: In this retrospective study, patients with HCM with an LVOT gradient ≥50mmHg after Valsalva manoeuvre and New York Heart Association (NYHA) class II-III symptoms were assigned to receive bisoprolol (starting at 1.25 mg daily). The initial dose was increased every two weeks to achieve the target in LVOT gradient <30 mmHg or the maximum tolerated dose. The primary endpoint was the achievement of a LVOT gradient <30 mmHg and ≥1 NYHA class improvement. The secondary endpoints were proportion of patients with LVOT gradient <30 mmHg or < 50 mmHg, proportion of patients with ≥1 NYHA class improvement, and change from baseline in LVOT gradient. Between December 2001 and December 2020, 92 patients were enrolled into the study. Sixteen (17%) patients on bisoprolol met the primary endpoint. Bisoprolol reduced the LVOT gradient to less than 30 mmHg in 33 (36%) patients, to less than 50 mmHg in 57 (62%), and improved NYHA class in 30 (33%). The mean reduction of LVOT gradient on bisoprolol was 28 (±14) mmHg and the percentage reduction was 42 (±21)%. In 35 (39%) patients, bisoprolol did not reduce the gradient to less than 50 mmHg requiring disopyramide and/or myectomy to achieve this goal. Conclusions: Treatment with bisoprolol was well-tolerated and effective in relieving obstruction and improving symptoms in a significant proportion of patients with symptomatic obstructive HCM.